Clinical predictors and outcomes of Klebsiella pneumoniae bacteraemia in a regional hospital in Hong Kong. Issue 1 (September 2017) - Man, M.Y.; Shum, H.P.; Chan, Y.H.; Chan, K.C.; Yan, W.W.; Lee, R.A.; Lau, S.K.P.
Summary: Background: Klebsiella pneumoniae (KP) infection is associated with high morbidity and mortality. Multidrug resistance, especially extended-spectrum β-lactamase (ESBL) production, in KP is endemic worldwide. Aim: To evaluate the clinical characteristics and outcomes of patients with KP bacteraemia in critical care and general ward settings. Methods: Adult patients admitted to a regional hospital in Hong Kong from January 1 st, 2009 to June 30 th, 2016 (7.5 years) with KP bacteraemia were included. Demographics, clinical features, microbiological characteristics, and outcomes were analysed. Findings: Among 853 patients, 178 (20.9%) required critical care and 176 (20.6%) died within 30 days of hospital admission. Thirty-day survivors were younger ( P  < 0.001), had milder disease (defined by Sequential Organ Failure Assessment score) ( P  < 0.001), presented with hepatobiliary sepsis ( P  < 0.001) or urosepsis ( P  < 0.001), less septic shock ( P  = 0.013), fewer invasive organ supports ( P  < 0.001), and had appropriate empirical antibiotics ( P  < 0.001). Cox regression analysis showed that respiratory tract infection (hazard ratio: 2.99; 95% confidence interval: 2.061–4.337; P  ≤ 0.001), gastrointestinal tract infection (excluding hepatobiliary system) (2.763; 1.761–4.337; P  ≤ 0.001), mechanical ventilation (2.202; 1.506–3.221; P  ≤ 0.001), medical case (1.830; 1.253–2.672; P  = 0.002), inappropriate empirical antibiotics (1.716; 1.267–2.324; P  ≤ 0.001), female (1.699; 1.251–2.307; P  < 0.001), age >65 years (1.692; 1.160–2.467; P  = 0.006), and presence of solid tumour (1.457; 1.056–2.009; P  = 0.022) were independent risk factors for 30-day mortality. Unexpectedly, diabetes mellitus was associated with better 30-day survival ( P  = 0.002). A total of 102 patients (12.0%) had infections with ESBL-producing strains, which were not associated with higher 30-day mortality. Conclusion: KP bacteraemia is associated with high 30-day mortality. Site of infection, patients' comorbidities and appropriate use of empirical antibiotic are important predictors of patients' outcomes.